Assessment of genetic diversity, detection of strain-specific single nucleotide polymorphisms and identification of the Bangladesh and Vietnam strain of Channa striata by PCR-RFLP analysis of the mitochondrial COI gene fragment - Md Samsul Alam; Foyjunnesa Projna; Mst. Sadia Zafrin; Rituparna Das; Mohd Golam Quader Khan (Aquaculture and Fisheries, 2022)
Striped snakehead (Channa striata) has enormous fisheries and aquaculture importance due to its high market demand and food value. Recently, Vietnam strain of the species has been introduced to Bangladesh for aquaculture. Therefore, it is essential to develop a reliable molecular technique that can distinguish the Bangladesh strain from the Vietnam ones as biological invasion by feral exotic fish to the wild may cause enduring damage to ecosystem and species diversity. Fin clips from snakehead samples were collected from six locations and total DNA was extracted. The cytochrome oxidase c 1 (COI) gene fragment was amplified by PCR using the Fish F1/R1 primer set and sequenced for analysis of intra- and inter-strain genetic diversity and detection of single nucleotide polymorphism to distinguish the Vietnam strain from Bangladesh ones. A total of 15 haplotypes were identified with an overall haplotype diversity of 0.888. The median-joining network created based on COI gene sequences clearly differentiated the Bangladesh strain from the strain of Vietnamese origin by a total of 18 single nucleotide polymorphisms. An In silico restriction analysis revealed AluI was the most suitable restriction enzyme that produced diagnostic restriction profiles of the two strains of C. striata. PCR-RFLP analysis by the restriction enzyme AluI created distinguishing restriction profile similar to that in the In silico analysis. This work illustrates a simple, reliable and inexpensive molecular tool for the identification of the Bangladesh and Vietnam strains of C. striata by one-step PCR and restriction of the COI gene fragment.